2022
DOI: 10.1111/ppc.13024
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of depression and sexual quality of life in postmenopausal women

Abstract: Purpose: To determine the prevalence of depression, review some variables that are believed to be associated and assess the relationships between depression and sexual quality of life in postmenopausal women.Design and Methods: This is a cross-sectional study conducted on postmenopausal women in Ankara, Turkey from February to June 2020. The study group consisted of 242 postmenopausal women. The Beck Depression Inventory and Sexual Quality of Life Questionnaire were used to assess the level of depression and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
(45 reference statements)
0
5
1
Order By: Relevance
“…For Tsai et al [25], somatic symptoms represented a risk factor for depressive syndrome in women. In this sense, the results of this study show that depression was directly related to the severity of climacteric symptoms, contrary to a study conducted in Turkey, which showed an indirect relation [15]. On the other hand, several studies showed that sexual function and climacteric symptoms were related [20,[26][27][28], contrary to our research.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…For Tsai et al [25], somatic symptoms represented a risk factor for depressive syndrome in women. In this sense, the results of this study show that depression was directly related to the severity of climacteric symptoms, contrary to a study conducted in Turkey, which showed an indirect relation [15]. On the other hand, several studies showed that sexual function and climacteric symptoms were related [20,[26][27][28], contrary to our research.…”
Section: Discussioncontrasting
confidence: 99%
“…In comparison, Yanikkerem et al [8] showed that 32% presented minimal symptoms. In addition, Duzgun et al [15] showed that mild symptoms were the most frequent. On the other hand, this study shows that around 90% of women reported some level of severity in sleeping alteration, contrary to what was found by Humeniuk et al [16], who indicated that 46% had no problems sleeping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women are more vulnerable to depressive disorders than men 21 . Meanwhile, depression is one of the most important problems among menopausal women 22,23 . In a meta‐analysis study conducted by Georgakis et al, it was observed that longer exposure to endogenous estrogens, such as older age at menopause and a longer reproductive period, is associated with a lower risk of depression in later life 24 .…”
Section: Introductionmentioning
confidence: 99%
“… 21 Meanwhile, depression is one of the most important problems among menopausal women. 22 , 23 In a meta‐analysis study conducted by Georgakis et al, it was observed that longer exposure to endogenous estrogens, such as older age at menopause and a longer reproductive period, is associated with a lower risk of depression in later life. 24 Nonetheless, in some studies, there is no relationship between menopausal age and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%